Values stories for Filipino children - Reyes, Fe Aida Lacsamana (Anvil, 2007)
"Hopefully this book, through its values-laden stories and activities, will help children gain self-confidence and belief in their innate goodness. Most of the stories here are true or have roots in my childhood in Davao. In reading these stories, I hope that the readers will be motivated to write and share their own stories or read similar ones from other sources."--Preface.